Eksperimentalno numerična analiza kavitacijskega toka okoli lopatičnega profila - Biluš, Ignacijo (Strojniški vestnik, 2005)
In this paper we present an analysis of the cavitation flow conditions around a NACA hydrofoil. The mathematical model, in the form of Navier Stokes equations, based on the additional transport equation for vapour mass fraction inception, propagation and condensation is presented for the mixture's (water - water vapour) properties. A simplified Rayleigh-Plesset equation is used when the phase change is modelled, where the parameters that influence the flow dynamics near the individual spherical bubble, surrounded by the liquid, are considered. Mathematical/physical model is included in the CFD code CFX 5.6. Simulation results are compared with experimental results from the cavitation tunnel, where the tested hydrofoil (blade) was placed.
Keywords: lopatice turbinske; tok kavitacijski; analize toka; simuliranje numerično; kavitacija; tokovne razmere; gibanje tekočin; matematični modeli